Effects of aromatase inhibitors letrozole and anastrazole on bone metabolism and steroid hormone levels in intact female rats - Kumru, Selahattin; Yildiz, Azer A.; Yilmaz, Bayram; Sandal, Suleyman; Gurates, Bilgin (Taylor & Francis Ltd, 2007)
Aim. The present study was designed to investigate the effects of two aromatase inhibitors on steroid hormone levels, bone mineral density (BMD) and bone turnover markers in intact female rats. Methods. Letrozole and anastrazole at two different dose levels were investigated for their effect on serum levels of estradiol, androstenedione, testosterone, dehydroepiandrosterone and dehydroepiandrosterone sulfate, BMD of femur and dorsal spine, and osteocalcin and pyridinoline levels as bone turnover markers. Fifty intact female rats were randomly divided in five groups (group 1 (n = 10): control, 2 ml saline; group 2 (n = 10): letrozole I mg/kg; group 3 (n = 10): letrozole 2 mg/kg; group 4 (n = 10): anastrazole 0. 1 mg/kg; group 5 (n = 10): anastrazole 0. 2 mg/kg), and oral gavages were applied for a period of 16 weeks. Results. Both doses of letrozole and anastrazole did not change femoral and vertebral BMD. Serum estradiol levels were reduced significantly at all dose levels by both agents (p < 0.001); all androgen levels were significantly elevated by letrozole (p < 0.05), although anastrazole increased only androstenedione (p < 0.05). The higher dose of letrozole increased osteocalcin levels (p < 0.05), while pyridinoline levels were increased (p < 0.05) by the higher dose of anastrazole. Conclusion. Our results indicate that short-term use of letrozole and anastrazole had no clear effects on BMD in intact rats. Further investigations are needed to understand their effects on bone metabolism in intact females.
7th International Congress of the Turkish-German-Gynecological-Association -- MAY 16-20, 2007 -- Antalya, TURKEY
Keywords: rat; letrozole; anastrazole; bone; osteocalcin; pyridinoline